Enregistrement et représentations de la stèle néolithique de L’Ouche de Beauce (Maisse, Essonne) - Serge Cassen; Valentin Grimaud; Laurent Lescop (Revue Archéologique du Centre de la France)
From now preserved and presented in the museum of Nemours, the Ouche de Beauce engraved stele (Maisse, Essonne) is a representative example of the elements of architecture and the neolithic iconographic programs inventoried in Gâtinais and in western border of the massif of Fontainebleau. The study would like to expose the various recordings techniques on the monolith and on the engravings, with the aim of a surface and chronological analysis of them, inside a three-dimensional model of the support. If the so-called anthropomorph representations on a face of the stele are peculiar to the considered geographical area, an even more abstract motive registered on the opposite face is clearly under the influence of the symbolic representations from Morbihan.